2018
DOI: 10.1038/s41388-017-0093-z
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-induced CD36 expression drives ovarian cancer progression and metastasis

Abstract: Ovarian cancer (OvCa) is characterized by widespread and rapid metastasis in the peritoneal cavity. Visceral adipocytes promote this process by providing fatty acids (FAs) for tumour growth. However, the exact mechanism of FA transfer from adipocytes to cancer cells remains unknown. This study shows that OvCa cells co-cultured with primary human omental adipocytes express high levels of the FA receptor, CD36, in the plasma membrane, thereby facilitating exogenous FA uptake. Depriving OvCa cells of adipocyte-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
320
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 382 publications
(352 citation statements)
references
References 59 publications
13
320
0
2
Order By: Relevance
“…Recently, multiple studies have shown that cancer cells with increased expression of fatty acid receptor, CD36, are able to initiate metastasis and promote self‐renewal . It is particularly noteworthy that omental adipocytes are able to induce expression of CD36 in ovarian cancer .…”
Section: Obesity and Age‐related Diseasesmentioning
confidence: 88%
“…Recently, multiple studies have shown that cancer cells with increased expression of fatty acid receptor, CD36, are able to initiate metastasis and promote self‐renewal . It is particularly noteworthy that omental adipocytes are able to induce expression of CD36 in ovarian cancer .…”
Section: Obesity and Age‐related Diseasesmentioning
confidence: 88%
“…Glycolysis and oxidative phosphorylation were measured with the Seahorse Extracellular Flux XF-96) analyzer (Seahorse Bioscience, North Billerica, MA) (Ladanyi et al, 2018). Cells were seeded in Seahorse XF-96 plates at a density of 10,000 cells per well and cultured for 24hr.…”
Section: Star Methodsmentioning
confidence: 99%
“…) or adipocytes (Ladanyi et al. ). We propose an additional role for sympathetic innervation of OMSs.…”
Section: Discussionmentioning
confidence: 99%